Polymetallic Complexes Part 91 Dimeric and Monomeric Complexes of CoII, NiII, CuII, ZnII, CdII and HgII with N∩O-O∩N and N∩O Donor Bis-bidentate and Bi-dentate Azodye Ligands - Mahapatra, Bi B; Sarangi, AK (Bangladesh Journal of Scientific and Industrial Research, 2011)
Bis-bidentate azodye, 4,4 / -bis (4/ -dihydroxyquinolincazo)3,3/ -dimethoxydibenzene having N∩O-O∩N donors and bidentate azodye (4 -hyoxyquinolineazo)4/ methoxybenzene having N∩O donors form dimeric and monomeric complexes of the type [M2LCl2(H2O)6], [M/2LCl2(H2O)2], [ML/2(H2O)2] and [M/L/2] where M = CoII, NiII, CuII; M /II, CdII, HgII. The complexes of the first and third categories are found to be six-coordinated with an octahedral and distorted octahedral configuration and the complexes of second and fourth type are four-coordinated with a tetrahedral geometry around the metal ions. The complexes have been characterised based upon analytical, conductance, magnetic susceptibility, i.r., electronic spectra, N.M.R., E.S.R. and X-ray diffraction data. The unit cell parameters like a, b, c, α, ß, γ and V (volume) have been calculated from the 2θ values. The unit cell geometry of the complex [Co2LCl2(H2O)6] is found to be monoclinic. Key words: Polymetallic complexes; Azodye complexes; Multidentate ligands. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.3558 Bangladesh J. Sci. Ind. Res. 46(2), 259-264, 2011